Democratic Leadership (Participative), Collaboration, Communication, Negotiation, Motivation and Job Satisfaction of Teachers and Education Staff - Purnama, Wahida; Muhammad, Muhammad; Agus, Agus (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to determine how the democratic leadership of the principal at Al-Wafa Preschool (PAUD) improves teacher performance. Data collection was conducted through interviews, observation, and documentation. The author employed qualitative research methods. The findings provide a description of the principal's managerial competencies for improving teacher performance, including: 1) The principal has excellent planning skills by involving deputies, other functional positions and the teacher council in the preparation of school plans which are carried out in the form of meetings held at the beginning of each new academic year. The principal prepares school plans such as the annual work plan (RKT) and the medium-term work plan (RKJM) which cover all areas needed by the school including improving teacher performance. 2) The principal has excellent leadership skills. The principal is very good at communicating, as seen from every meeting the principal holds every week with teachers and staff to evaluate and plan activities to be carried out in the following week. 3) The principal has excellent leadership skills. The principal is very good at conveying tasks and providing input to school staff and the teacher council. The principal is also always open and happy to accept input or opinions from others. A positive personality also makes it easier for the principal to lead the school, especially in creating a work climate for teachers. 4) The principal of Al-Wafa manages teachers and staff quite well. The principal carries out planning, direction, and always strives to provide the facilities needed by teachers and staff. The principal has also procured facilities and infrastructure well, but maintenance, repairs, and disposal of these facilities and infrastructure have not been carried out optimally. 5) The principal makes several efforts to improve teacher performance, namely by providing the best possible school facilities to facilitate teachers' tasks, maintaining good communication with teachers, providing training to teachers in each field they are responsible for, including in-house training (IHT) and MGMP programs. The principal also conducts supervision and assessments to determine teacher performance results and provides awards to qualified and high-achieving teachers.